A Silurian-early Devonian slab window in the southern Central Asian Orogenic Belt: Evidence from high-Mg diorites, adakites and granitoids in the western Central Beishan region, NW China. (March 2018) - Zheng, Rongguo; Xiao, Wenjiao; Li, Jinyi; Wu, Tairan; Zhang, Wen
Graphical abstract: Highlights: There are Silurian-early Devonian plutons in the western Central Beishan region. These plutons were derived from magmas generated in a subduction zone environment. A slab window was associated with massive crustal growth in the southern CAOB. Abstract: The Beishan orogenic belt is a key region for deciphering the accretionary processes of the southern Central Asian Orogenic Belt. Here in this paper we present new zircon U–Pb ages, bulk–rock major and trace element, and zircon Hf isotopic data for the Baitoushan, and Bagelengtai plutons in the western Central Beishan region to address the accretionary processes. The Baitoushan pluton consists of quartz diorites, monzonites and K-feldspar granites, with zircon LA–ICP–MS U–Pb ages of 435 Ma, 421 Ma and 401 Ma, respectively. The Baitoushan quartz diorites and quartz monzonites exhibit relatively high MgO contents and Mg# values (63–72), display enrichments in LILEs and LREEs, and exhibit high Ba (585–1415 ppm), Sr (416–570 ppm) and compatible element (such as Cr and Ni) abundances, which make them akin to typical high-Mg andesites. The Baitoushan quartz diorites and quartz monzonites were probably generated by the interaction of subducted oceanic sediment-derived melts and mantle peridotites. The Baitoushan K-feldspar granites are ascribed to fractionated I-type granites with peraluminous and high-K calc-alkaline characteristics. They exhibit positive εHf (t) values (2.43–7.63) and Mesoproterozoic–Neoproterozoic zircon Hf model ages (0.92–1.60 Ga). Those early Devonian granites, including Baitoushan K-feldspar granite and Gongpoquan leucogranites (402 Ma), are derived from melting of the mafic lower crust and/or sediments by upwelling of hot asthenospheric mantle. The Bagelengtai granodiorites exhibit similar geochemical signatures with that of typical adakites, with a zircon SHRIMP U-Pb age of 435 Ma. They exhibit relatively high Sr (502–628 ppm) and Al2 O3 (16.40–17.40 wt.%) contents, and low MgO (1.02–1.29 wt.%), Y (3.37–6.94 ppm) and HREEs contents, with relatively high Sr/Y and (La/Yb)N ratios. The Bagelengtai granodiorites were derived from partial melting of subducted young oceanic crust, with significant contributions of subducted sediments, subsequently hybridized by the mantle peridotite. On the basis of our data and combined with previous data, we conclude that a Silurian–early Devonian slab window model accounts for all geological records in the western segment of the Central Beishan. We further propose that magmatic events associated with a slab window played an important role in crustal growth of the Central Asian Orogenic Belt.